IMPROVING THE QUALITY OF EDUCATION IN THE COVID-19 ERA THROUGH THE IMPLEMENTATION OF ONLINE LEARNING RESOURCES WITH POE2WE MODEL ON PARABOLIC MOTION - Vina Serevina; Raida Raida (International Journal of Educational Management and Innovation, 2021)
The Covid-19 pandemic has affected all aspects of life, also education. Educators worldwide have had to adapt the situation by developing online learning models to keep education running. The present study aims at developing online learning resources using websites and the POE2WE model of parabolic motion material. The POE2WE model was represented as six stages of online learning that includes Prediction, Observation, Explanation, Elaboration, Write, and Evaluation. 30 students of 10th grade of a high school in Indonesia participated in this study. The ADDIE model (analyzing, designing, developing, implementing and evaluating) used in this study representing its R&D methodology with the evaluating stage carried out in every other stage. The online learning model validated with three different experts, namely media, material, and learning expert resulting in 89.40%, 89.31%, and 86.71%. The results indicated that the model was valid and reliable. Pre-test and post-test conducted to investigate the effects of the learning model, which resulted in 40.03% and 82.73% respectively, with the N-gain mean result in high category (0.71). It can conclude that the online learning model developed in this study was effective in increasing students understanding of parabolic motion.